Підхід до раціоналізації регіонального розвитку продуктивних сил України - Мамчин, М. М.; Патора, Р. (Видавництво Львівської політехніки, 2017)
Обґрунтовано необхідність комплексного удосконалення регіональної системи організації продуктивних сил. Водночас сама система повинна бути оптимальною з погляду неухильного підвищення продуктивності праці, досягнення збалансованості між структурою трудових ресурсів і структурою робочих місць, оптимальним використанням предметів і засобів уречевленої праці і повною мірою враховувати особливості досліджуваної території. Самостійне значення має розвиток цієї системи стосовно проміжних і низових рівнів обласного розділення, диференціація її в повній номенклатурі регіональних одиниць – економічних округів і локальних соціально- економічних одиниць. Встановлено, що основою розвитку округів мають бути локальні соціально-економічні комплекси. На основі проведених досліджень виявлено, що округи, будучи важливими локальними структурними елементами обласної системи розселення і обласної системи організації продуктивних сил, можуть становити об’єктивну основу раціоналізації регіонального розвитку продуктивних сил. За результатами аналізу організації продуктивних сил Львівської області виокремлено шість економічних округів: Львівський, Дрогобицький, Золочівський, Самбірський, Стрийський і Червоноградський. Пропонована система, яка охоплює територіальну організацію виробництва і територіальну систему розселення, може стати одним із підходів до раціоналізації й ефективного використання продуктивних сил регіону і сприяти створенню повноцінного життєвого середовища для його жителів.

In this article is described necessity of complex improvement for an a regional organization system of the productive forces. This system by itself has to be optimal in terms of the steady increase productivity of work, achieve a balance between the structure of human resources and the structure of job places, the best use of objects and tools of materialized labor and fully take into account the peculiarities of the study area. Self-importance has the development of the system with regard to the intermediate and grassroots levels of regional division, differentiation of the full range of regional units – economic counties and local socio-economic units. It was established that the basis of districts should form local socio-economic systems. Based on the results of research it was found, that regions, being local important structural elements of the regional system of resettlement and regional system of productive forces, can make an objective basis for the rstreamline of regional development of the productive forces. The analysis of the productive forces of the Lviv region made it possible to distinguish the six economic areas – Lviv, Drohobych, Zolochiv, Sambir, Stryi and Chervonograd. The system which covers the territorial organization of the production system and territorial settlement could be one of the approaches to streamline and efficient use of the productive forces of the region and promote the creation of a complete living environment for its residents. The purpose of this article is to present results of the study perticularies of regional development and the allocation of Ukraine grassroots integrated economic units (districts), which will increase the efficiency of regional modernization. So proposed in article approach to the productive forces of the regional level with the release of grassroots units of differentiation – economic districts will fully take into account the peculiarities of the study area, optimize the use of available resources and on this basis to achieve the welfare of the region, the growth of cultural and technical level, reduce unemployment. The basis of districts should form local socio-economic systems, which will have to become important local structural elements of the regional system of settlement and regional system of productive forces. Due to that, growing need to increase the role of local authorities and planning. In the center of the district important to focus the work of prospective and current planning and management of development of the productive forces on the territory of each particular district, and in the regional center should be made coordination of district authorities to the rational use of resources throughout the regional system.
Approach to regional development rationalization of productive forces in Ukraine
Keywords: продуктивні сили; економічний округ; організація продуктивних сил; соціально-економічний комплекс; система розселення; productive forces; the economic district; organization of the productive forces; socio-economic complex; settlement system; 332.021